The Effect of Risk Based Internal Audit on Financial Performance of Commercial Banks in Uganda: A Case Study of Stanbic Bank Uganda Ltd – Mukono Branch - Salimat Apio (Uganda Christian University, 2023)
The study investigated the effect of risk based internal audit on financial performance of commercial banks in Uganda; particularly in Stanbic Bank Uganda Ltd. The study was guided by the following objectives: to examine the effect of risk management on financial performance; to assess the role of audit compliance on financial performance; to establish the relationship between risk mitigation and financial performance. The study adopted a descriptive research design to obtain information. It focused on a target population of 40 employees where a sample size of 30 respondents was selected. The researcher collected data from both primary and secondary data collection sources and this was done by using questionnaires and interview guides as data collection instruments The study revealed that respondents agreed that risk management practices had an effect on the performance of commercial banks as shown by the overall mean of 3.894 and standard deviation of 0.404. It also shows in this study that the participants agreed that internal auditing capacity lanning had an impact on performance of the commercial banks as shown by the average mean of 3.596 and standard deviation of 0.486. Results from the regression analysis showed the 74% of the variation on return on equity was due to risk based audit, inflation and annual GDP. Further the results showed that the model fit with risk based audit, inflation and annual GDP as predictor variables was statistically significant to predict return on equity. The regression findings also showed that risk based auditing and annual GDP rate showed a beneficial effect which was positive on ROE while inflation rates had an unfavorable effect which was negative on the ROE The researcher recommended; that the management of the commercial banks should embrace measures that promote risk based auditing the firms, the management should also ensure establishment of an effective risk evaluation strategy to ensure that the institutions are able to operate proficiently in the market, The study also recommended that the government through the central bank should put in place measures and policies to make sure there is a beneficial operation of the markets. It is in such an environment that the annual GDP growth can be realized and inflation rate kept in check to ensure optimal operation of financial institutions
This is a dissertation.